Evaluation of Clinical and Pathologic Risk Factors May Reduce the Rate of Multimodality Treatment of Early Cervical Cancer. (February 2016) - Gemer, Ofer; Lavie, Ofer; Gdalevich, Michael; Eitan, Ram; Mamanov, Ela; Piura, Benjamin; Rabinovich, Alex; Levavi, Hanoch; Saar-Ryss, Bozhena; Halperin, Reuvit; Finci, Shachar; Beller, Uzi; et al.
Abstract : Objective: To assess the rate of postoperative adjuvant treatment in patients who underwent radical hysterectomy for early cervical cancer and to suggest criteria for the triage of patients who have a high probability of multimodality treatment. Methods: This was a multicenter retrospective study of 514 patients with FIGO stages IA2-IIA cervical cancer who underwent radical hysterectomy between 1999 and 2010. The patients were divided into 2 groups according to whether or not postoperative radiation was administered. The 2 groups were compared with regard to clinical and histopathologic variables divided into major and minor criteria (intermediate risk factors) based on lymph nodes status, parametrial involvement, tumor size, deep stromal invasion, and lymph-vascular space invasion. Results: We identified 294 (57.2%) patients who received adjuvant postoperative radiotherapy (RT) or chemoradiation. Fifty-three percent of these patients who were treated by adjuvant radiation had only intermediate risk factors. Combining the various combinations of 2 out of 3 of the following criteria, we found that 89% of patients with tumors ≥2 cm and lymph-vascular space invasion received RT, 76% of patients with tumors ≥2 cm and depth of invasion >10 mm received RT, and 87% of patients with tumors depth of invasion >10 mm and lymph-vascular space invasion received RT. Conclusions: This study suggests that in patients with early cervical cancer, clinicopathologic evaluation of tumor size and lymph-vascular space invasion should be undertaken before performing radical hysterectomy. This approach can serve to tailor treatment, reducing the rate of employing both radical hysterectomy and chemoradiation.